Body armor for stab and spike protection, Part 2: a review of test methods. Issue 16 (August 2019) - Nayak, Rajkishore; Crouch, Ian; Kanesalingam, Sinnappoo; Wang, Lijing; Ding, Jie; Tan, Ping; Lee, Bin; Miao, Menghe; Ganga, Deepak; Padhye, Rajiv
In many countries, stabbing is still the most common cause of homicide. It is difficult to quantify the magnitude of the force used in a stabbing incident by an alleged assailant. Pathologists describe the stabbing force using relative subjective terms, such as mild, moderate, considerable or severe. More precise objective evaluation of the severity of stabbing is very important for quantitative understanding of stab wounds and for scientific assessment of the effectiveness of stab-resistant armor. In this perspective review, the standard objective methods used for the quantification of the protection provided by the stab and spike or puncture resistant materials are described. In addition, the nonstandard test methods developed by various research organizations have also been discussed. This paper is a follow-up to the previous paper (Body armor for stab and spike protection, Part 1: scientific literature review) published in the Textile Research Journal . Special emphasis has been given to the recent developments in both test standards and experimental methodologies used to evaluate stab and spike protection. This paper has systematically reviewed the standard test methods used for evaluating the stab and spike protection performance of body armor for comparisons. Furthermore, the backing materials, which are used for stab and puncture resistance tests to quantify the back-face deformation, were highlighted. Also, the approach for the wearer's trial to predict the performance was discussed. This paper will provide guidelines to researchers, manufacturers and defense department working in the area of design and fabrication of body armor systems.